Peraturan pemerintah nomor 24 tahun 2005 tentang standar akuntansi pemerintahan - [Tidak Terdaftar] (Salemba Empat, 2005)
Peraturan pemerintah nomor 24 tahun 2005 tentang standar akuntansi pemerintahan